2005
DOI: 10.4049/jimmunol.175.7.4555
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to Fibrillin-1 Activate Normal Human Fibroblasts in Culture through the TGF-β Pathway to Recapitulate the “Scleroderma Phenotype”

Abstract: Fibroblasts from patients with systemic sclerosis (SSc) are activated producing excessive amounts of extracellular matrix (ECM) components. Recently, we identified a new SSc-specific autoantibody against portions of fibrillin-1, a major component of ECM microfibrils and regulator of TGF-β1 signaling. To examine a potential pathogenic role of anti-fibrillin-1 autoantibodies, normal human fibroblasts were treated with affinity-purified autoantibodies isolated from SSc sera and then examined for alterations in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
2
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 34 publications
1
46
2
5
Order By: Relevance
“…Therefore, one may consider that anti-fibrillin autoantibodies are present and play a role in liver fibrosis. It was recently shown that anti-fibrillin-1 autoantibodies from scleroderma patients may play a pathogenic role by increasing the transcription and production of ECM components in normal human fibroblasts via the release of sequestered TGF-β1 from fibrillin-1 (26).…”
Section: The Mechanism Of B Cell Involvement In Liver Fibrosis Remainmentioning
confidence: 99%
“…Therefore, one may consider that anti-fibrillin autoantibodies are present and play a role in liver fibrosis. It was recently shown that anti-fibrillin-1 autoantibodies from scleroderma patients may play a pathogenic role by increasing the transcription and production of ECM components in normal human fibroblasts via the release of sequestered TGF-β1 from fibrillin-1 (26).…”
Section: The Mechanism Of B Cell Involvement In Liver Fibrosis Remainmentioning
confidence: 99%
“…Other investigators have identified AFAs in patients with SSc, mostly in those with the diffuse form of the disease (23), and it was observed that IgG in patients with SSc and pulmonary arterial hypertension (PAH) recognized fibroblast components that were distinct from those in patients with primary PAH (24). In addition, SSc autoantibody binding to the nonstructural matrix component fibrillin 1 (25), as well as to the adhesion molecule NAG-2 (26,27) and to the platelet-derived growth factor (PDGF) receptor (28) expressed on fibroblasts, results in activation of these components, accompanied by increased collagen synthesis. Upon PDGF receptor binding, SSc autoantibodies enhance production of reactive oxygen species and induce phosphorylation of ERK-1/2 (28).…”
mentioning
confidence: 99%
“…Antikörper gegen Matrix-Metalloproteinasen können ihre Zielantigene hemmen und dadurch die Balance zwischen Kollagenauf-und -abbau zuungunsten der Degradation verschieben [33,38]. Fibrillin-Antikörper sollen durch Interferenz mit extrazellulären Mikrofibrillen die Freisetzung von latentem TGF-β und eine durch diesen vermittelte profibrotische Genregulation auslösen [48]. …”
Section: Pathogenetische Bedeutung Sklerodermie-assoziierter Autoantiunclassified